Kompetensi pengurusan dan pelaksanaan kokurikulum dalam kalangan penolong kanan kokurikulum di sekolah-sekolah menengah daerah Kota Kinabalu - Alizah, Abdul Majid (2010)
This study aimed to identify the competencies and levels of management and implementation of the Senior Assistant Co curriculum. The sample consists of 17 Senior Assistant Co, 17 principals and 68 Coordinating Unit Co-curriculum of secondary schools in the district of Kota Kinabalu which comprises of school (a) One and two conference (b) Number of students more than 1000 and less than 1000. Information related to the level of competence and level of curriculum offered by the management of three perceptions of (a) Senior Assistant Co-curriculum perception, and (b) Principal perception (c) Co-Curriculum Unit Coordinator perception. Practice Management Senior Assistant Co-curriculum is based on the principles of management, namely planning, leading, controlling and evaluating. Questionnaires based on Likert scale is used as the survey method to collect and analyze data in this study will be conducted. Descriptive statistics were used to answer research questions, while the inferential statistics, t-test, One Way ANOVA and Pearson Correlation test used to test the hypothesis. The study showed that the level of competence and level of management and implementation of the Senior Assistant Cocurriculum in all aspects at a high level. T-test showed significant difference between the levels of Senior Assistant Co-curriculum competencies in the school first and second press conference and there was no significant difference in the levels of management and implementation of Senior Assistant Co-curriculum in schools with more students in 1000 with the Senior Assistant of Co-curriculum in schools has 1000 pupils. One Way ANOVA test showed significant difference between the mean of five years experience with min 1-5 years of experience mean that the group had been less than a year. The Pearson correlation test showed significant correlation between the levels of Senior Assistant Co-curriculum competencies with the management and implementation by the Senior Assistant Co-curriculum. The analysis of students' achievements, the school a conference be achieved Grade A and Grade B is higher than the performance of two conference schools. This shows the level of Senior Assistant Co-curriculum competencies related to student achievement